223k views
4 votes
53(2x−6)+18=23(x+3)−4.

User DFriend
by
5.0k points

2 Answers

3 votes

Answer:

x = 365/83

Explanation:

53(2x−6)+18=23(x+3)−4

106x-318+18=23x+69-4

106x-23x=69-4+318-18

83x = 365

x = 365/83

User Karyon
by
4.9k points
2 votes

Answer:

365/83

Explanation:

Distribute where we can

106x - 318 + 18 =23x + 69 - 4

Get variables on one side and constants on the other

106x - 23x = 65 + 300

Do the math

83x = 365

Divide both sides by 83

365/83

User ThiagoLeal
by
4.6k points